Quality control by infrared thermography of the infusion manufacturing process of composite automotive specimens. Issue 2 (3rd July 2017) - Venegas, P.; Ortiz de Mendibil, I.; Montero, A.; Aurrekoetxea, J.
Abstract : In this study the main defects appearing in composite manufacturing by infusion process are investigated to develop specific quality control routines. The technology employed to analyse this process and carry out quality controls is infrared thermography which, due to the special configuration of infusion manufacturing, allows an on-line monitoring of the whole process. This study was conducted at laboratory level with different composite materials, determining the thermal behaviour of the zones undergoing anomalies. This way a complete procedure for anticipating defect initialization and stopping the manufacturing process in early stages was defined, enabling repair actions and saving time and costs.